Biomechanical changes following corneal crosslinking in keratoconus patients - Felter, Emilia; Khoramnia, Ramin; Friedrich, Maximilian; Son, Hyeck Soo; Auffarth, Gerd U.; Augustin, Victor A. (Graefe's archive for clinical and experimental ophthalmology, 2024)
Purpose: To evaluate the biomechanical and tomographic outcomes of keratoconus patients up to four years after corneal crosslinking (CXL). Methods: In this longitudinal retrospective-prospective single-center case series, the preoperative tomographic and biomechanical results from 200 keratoconus eyes of 161 patients undergoing CXL were compared to follow-up examinations at three-months, six-months, one-year, two-years, three-years, and four-years after CXL. Primary outcomes included the Corvis Biomechanical Factor (CBiF) and five biomechanical response parameters obtained from the Corvis ST. Tomographically, the Belin-Ambrósio deviation index (BAD-D) and the maximal keratometry (Kmax) measured by the Pentacam were analyzed. Additionally, Corvis E-staging, the thinnest corneal thickness (TCT), and the best-corrected visual acuity (BCVA) were obtained. Primary outcomes were compared using a paired t-test. Results: The CBiF decreased significantly at the six-month (p < 0.001) and one-year (p < 0.001) follow-ups when compared to preoperative values. E-staging behaved accordingly to the CBiF. Within the two- to four-year follow-ups, the biomechanical outcomes showed no significant differences when compared to preoperative. Tomographically, the BAD-D increased significantly during the first year after CXL with a maximum at six-months (p < 0.001), while Kmax decreased significantly (p < 0.001) and continuously up to four years after CXL. The TCT was lower at all postoperative follow-up visits compared to preoperative, and the BCVA improved. Conclusion: In the first year after CXL, there was a temporary progression in both the biomechanical CBiF and E-staging, as well as in the tomographic analysis. CXL contributes to the stabilization of both the tomographic and biomechanical properties of the cornea up to four years postoperatively.
Gesehen am 15.11.2024